(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The text proposes and explicates the arguments which support the hypothesis concerning the professional sign on a ring from the necropolis in Vodoča near Strumica. The bronze ring is simple; however, on the head, which also served as a seal, there is a carved depiction of a scorpion. A detailed analysis indicates that its bearer was probably a member of the military crew which during sieges operated the catapult-type weapons/ spring engines known as ‘scorpions.’ The morphological characteristics of the ring suggest that it dates to the late 14th century, although it is undoubted that it must have been used in the first half of the 15th century as well.